Is the post-communist transition over? - Elodie Douarin; Tomasz Mickiewicz (IZA World of Labor, 2022)
An extensive program of economic liberalization reforms, even when it generates positive outcomes, does not automatically generate support for further reforms. Societies respond with strong support only after experiencing the effects of reversing these reforms (i.e. corruption, inequality of opportunity). This point is illustrated through the example of the post-communist transformation in Eastern Europe and Central Asia—arguably a context where the end point of reforms was never clearly defined, and even successful reforms are now associated with a degree of reform suspicion.
Keywords: O52; P20; P26; P27; P30; 330; development; convergence; post-communist transformation; transition; reforms; EU